Health research internships: Pasantías de investigación en salud - De La Cruz Vargas, Jhony Alberto (2019)
The Faculty of Human Medicine and the Research Institute in Biomedical Sciences of the University Ricardo Palma, has been participating as Headquarters of the Student Mobility Program of the Peruvian Network of Student Teaching Mobility in REPEMIDE Medicine, constituted by the Peruvian Association of Faculties of Medicine ASPEFAM. We were pilot center in 2017-2018, receiving medical students from various universities of the country, with the "Health Research Internship", and in the 2018-2019 call we received 4 medical students selected from Peruvian universities. DOI:10.25176/RFMH.v19.n2.2081